Three-layered films enable efficient passive radiation cooling of buildings - Guo Yi (e-Polymers)
To address the excessive energy consumption of building cooling, the coverage of passive radiation cooling materials on the surface of buildings can effectively save the global refrigeration power resources and reduce the greenhouse gas emissions generated by refrigeration equipment. In this work, passive radiation hydrophobic fabric cooling materials with three functional layers (i.e., top polydimethylsiloxane [PDMS] film layer for solar emissivity, middle polymethylmethacrylate [PMMA] film layer for solar reflectivity, and bottom cotton fabric layer for support) were prepared. This passive radiation cooling material with optimized thickness of PDMS (1.5 mm) and PMMA (3.5 mm) have a rich uneven filament structure and ideal internal bonding structure, which enabled 94% of solar reflectivity and 93.4% of atmospheric window emissivity (8–14 μm). Top layer of the composite film was hydrophobic (a contact angle of 117°) and allowed the rolling of water droplets to remove most of the surface dust. Moreover, these composites presented an excellent cooling of 7.7–15.0°C in the outdoor real cooling test. For medium-sized houses, the roof covered with composite was expected to reduce the emission CO2 by 17% every year. The findings of this work indicated that the prepared three-layered radiation cooling materials have great potentials in thermal energy storage buildings.